Liens personnels, réseaux, solidarités en France et dans les îles Britanniques (xie-xxe siècle) - David, Bates; Véronique, Gazeau (Homme et société, 2006)
Rivalries and conflicts have left a deep mark on the history of relations between France and Britain and still hold a major place in the historiography. The study of personal links, networks and interdependencies within an intellectual context marked by the influence of social sciences may open up some new prospects and help to reconstruct some cross-Channel exchanges which the documentation does not always allow us to grasp directly Thanks to comparative work, it may also renew the understanding of some phenomenons which Trench and British historians have tended to study in isolation. The round table organised by the Groupe de Recherche "France-îles Britanniques " (CNRS 2136) in Glasgow in May 2002 took up this theme: the sixteen papers gathered in this volume analyse notions such as the individual and kinship, friendship, neighbourhood relationships, courts, noble entourages, affinities and clienteles, and literary circles, using sources as different as public acts, correspondence, heraldry, iconography, narrative sources or diaries. The deliberate choice of a "longue durée", from the Middle Ages to the twentieth century, also makes possible the confrontation of contrasting social evolutions and historiographical methods. The use of different grids of interpretation, whether network analysis or prosopography brings to light networks that would otherwise remain hidden, or which were activated only in specific circumstances, such as succession: it also enables the historian to get a better understanding of developments such as scientific invention or the circulation of political ideas. It is indeed at the conjunction of different approaches and experiences that the concept of "network" may be most effective.